Pengembangan Aplikasi Presensi (Studi Kasus Aplikasi Andalasian Di Universitas Andalas) - Putra Prima Suhendri, Ade (CV. Shofanah Media Berkah, 2024)
The COVID-19 pandemic has led to changes in the education system at Andalas University, requiring a shift from traditional face-to-face learning to online platforms to ensure compliance with legal mandates. To address attendance tracking concerns arising from the pandemic, the university developed the Andalasian app which integrates geolocation and face recognition technology. This study explores the development and implementation of the Andalasian app, discussing its features and deployment through web and mobile platforms. By leveraging the Software Development Life Cycle (SDLC) methodology, the app offers efficient attendance tracking while minimizing the risk of COVID-19 transmission. The research results demonstrate its effectiveness, with significant downloads and positive feedback from users, making attendance management at Andalas University easier.